Institutional Requirements and Policy Processes for Establishing Managed Migration with and in Afghanistan - Smith, Rebekah Lee (World Bank, Washington, DC, 2018)
International labor migration is becoming an increasingly important employment strategy for developing countries. However, while increasing mobility creates huge potential increases in global welfare, accessing these gains requires careful management and facilitation of labor flows to avoid low-level equilibria. Sending countries will need to design labor-sending systems that balance increased mobility with protection throughout the entire migration process, while ensuring that supply and demand for specific skills are matched. This note proposes a structure for designing a labor-sending system and applies this structure to an assessment of the existing labor-sending system in Afghanistan, which is currently in very nascent stages and is missing many fundamental elements. It then applies the findings of this assessment to propose a way forward in building Afghanistan’s labor-sending system, along with an estimate of how long it will take for the system to become operational.